The power of shared positivity: organizational psychological capital and firm performance during exogenous crises - Ann-Christin Grözinger; Sven Wolff; Philipp Julian Ruf; Petra Moog (Small Business Economics, 2021)
This study examines the influence of organizational psychological capital on the performance of small and medium-sized companies (SMEs) during crises. We argue that SMEs use their intangible resources to cope with difficult situations such as the COVID-19 pandemic. Therefore, we investigate how organizational psychological capital impacts performance and creative innovation through such intangible resources, namely, organizational citizenship behavior, solidarity, and cooperation. Methodologically, we combine structural equation modelling and regression analysis on a dataset of 379 SMEs. Our results support the notion that organizational psychological capital positively influences creative innovation of SMEs and thus performance during crises. Our research contributes to the organizational behavior literature by showing that psychological resources of SMEs can strengthen performance in times of crisis and help to prepare for future ones.
Keywords: L20; L25; L26; 330; Crisis; Individual psychological capital; Organizational psychological capital; Performance; Creativity; Organizational citizenship behavior